Effect of Maximum Aggregate Size on the Strength of Normal and High Strength Concrete - Gaith Abdulhamza Mohammed; Samer Abdul Amir Al-Mashhadi (Civil Engineering Journal, 2020)
Aggregates form 60% to 75% of concrete volume and thus influence its mechanical properties. The strength of (normal or high-strength) concrete is affected by the maximum size of a well-graded coarse aggregate. Concrete mixes containing larger coarse aggregate particles need less mixing water than those containing smaller coarse aggregates, In other words, small aggregate particles have more surface area than a large aggregate particle. In this research, about twenty-two mixtures were covered to study the effect of the MSCA, on compressive strength of (normal strength concrete) and Sixteen mixtures to study the effect of the maximum size of coarse aggregate on compressive strength for (high strength concrete). The concrete mixture is completely redesigned according to the maximum size of coarse aggregate needs and maintaining uniform workability for all sizes of coarse aggregate. The American design method was adopted ACI 211.1, for normal concrete. ACI 211-4R, the design method was adopted for high strength concrete. And use the MSCA with dimensions (9.5, 12.5, 19, 25, 37.5, and 50) mm for normal strength concrete and the MSCA (9.5, 12.5, 19, and 25) mm for high strength concrete. The slump was fixed (75-100) mm for normal strength concrete. Slump is fixed to (25-50) mm for high strength concrete before added Superplasticizer high range water reducer (HRWR). With Fineness Modulus (F.M) fixed to 2.8 for both normal concrete and high-strength concrete. According to the results of the tests, the compressive strength increases with the increase in the MSCA, of the normal concrete and also high – strength concrete. And the effect of the MSCA, on the compressive strength of normal concrete, is higher than that of high-strength concrete.